Evaluasi Pengendalian Internal dalam Sistem Informasi Akuntansi terhadap Penerimaan dan Pengeluaran Kas Studi Kasus PT Bank Sumut Syariah Cabang Medan Katamso - M. Reza Shah Fahlevi Lubis; Hendra Harmain; Wahyu Syarvina (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This research is to find out the Evaluation of Internal Control in the Accounting Information System on Cash Receipts and Disbursements Case Study of Pt. Bank Sumut Syariah Medan Katamso Branch. This study uses qualitative research methods and data collection techniques with interviews and documentation techniques. This study uses data collection techniques by interviewing several employees at Pt. Bank Sumut Syariah Medan Katamso Branch. The results of this study indicate that the internal control system for cash receipts and disbursements has been implemented by PT. Bank Sumut Medan Katamso Branch which has fulfilled the cash receipt and disbursement requirements. internal control system The effectiveness of cash receipts is not yet effective. At PT. Bank Sumut Medan Katamso Kota Branch, the capacity of the accounting information system to handle cash receipts and disbursements is inadequate so that the company's internal cash management becomes ineffective because the accounting and finance departments continue to play a complementary role